 i need more help with math please!? - XP Math - Forums Sign Up FREE! | Sign In | Classroom Setup | Common Core Alignment  XP Math - Forums i need more help with math please!? 07-17-2007 #1 Jules Guest   Posts: n/a i need more help with math please!? what is? FOIL 1. (x+4)(x-2) = 2. (-2x-3)(3-x) = 07-17-2007 #2 Knock N Guest   Posts: n/a Multiply: First Outter Inner Lastx * x -2x 4x -8 07-17-2007 #3 gabriel070286 Guest   Posts: n/a 1. (x + 4) (x - 2) = x*x - 2x + 4x -8= x^2-2x+4x-8 = x^2+2x-82. (-2x-3) (3-x)= -2x* 3 + 2x*x-3*3 + 3*x=-6x+2x^2-9+3x= 2x^2-3x-9 07-17-2007 #4 ehhh.... Guest   Posts: n/a F irstO uterI innerL astu multiply the first numbers or x in parenthesis, the the outer numbers, then the inner, then the lastx^2+4x-2x-8= x^2+2x-8-6x+2x^2-9+3x= 2x^2-3x-9 07-17-2007 #5 â™¥ Dani Guest   Posts: n/a FOIL stands for First, Outer, Inner, Last. It's the order you can use to solve those problems.Multiply the first terms in each set of parentheses (in #1, the 2 x's). Then multiply the 2 terms on the outside (in #1 this is the first x and the -2). Then multiply the inner terms (in #1 these are the second x and the 4). Last, multiply the last terms (in #1 it's the 4 and the -2).1. (x + 4)(x - 2) = (first) x^2 (outer) -2x (inner) +4x (last) -8= x^2 - 2x + 4x + 8 __ clean this up a bit by adding like terms.= x^2 + 2x - 8And there you have it. You can do #2 in the same way.(-2x - 3)(3 - x) = (first) -6x (outer) +2x^2 (inner) -9 (last) +3xreorder that a bit... = 2x^2 - 6x + 3x - 9 ... and add like terms.so #2 = 2x^2 - 3x + 9 07-17-2007 #6 blossom Guest   Posts: n/a 1. x2 + 4x - 2x - 8 = x2 + 2x -82. (-2x-3)(-x+3)= 2x2 + 3x - 6x - 9 = 2x2 - 3x - 92x2 meaning 2x squared. Don't know how to make the 2 superscript. 07-17-2007 #7 txmama423 Guest   Posts: n/a foil=multiply the first terms, then the outer, then the inner terms & then the last terms; 1. (x+4)(x-2)=x^2-2x+4x-8(combine like terms now),= x^2+2x-82. (-2x-3)(3-x)= 2x^2-6x+3x-9= 2x^2-3x-9 07-17-2007 #8 febbfish Guest   Posts: n/a 1. For expansion you multiply the terms 1 by 1..(x+4)(x-2) = (x * x) + [x * (-2)] + [(+4) * x] + [(+4) * (-2)] = x^2 + (-2x) + (4x) + (-8) = x^2 - 2x + 4x - 8 = x^2 + 2x - 8Take note of the signs when you open the brackets.2. (-2x-3)(3-x) = [(-2x) * 3] + [(-2x) * (-x)] + [(-3) * 3] + [(-3)* (-x)] = (-6x) + (2x^2) + (-9) + (3x) = -6x + 2x^2 - 9 + 3x = 2x^2 - 3x - 9Remember the sign belongs to the term behind the sign. 07-17-2007 #9 curiosity2414 Guest   Posts: n/a 1)(x+4)(x-2)x^2+2x-82)(-2x-3)(3-x)-6x^2-9+2x+3x=-6x^2+6x-9 07-17-2007 #10 calpal2001 Guest   Posts: n/a 1. (x + 4) (x - 2) = x^2 +4x - 2x - 8= x^2 + 2x - 8x = -4, 22.(-2x - 3)(3 - x) = -6x - 9 + 3x + 2x^2= -9 - 3x +2x^2= 2x^2 - 3x - 9x = - 3/2 , 3

 Thread Tools Show Printable Version Email this Page Display Modes Linear Mode Switch to Hybrid Mode Switch to Threaded Mode Posting Rules You may not post new threads You may not post replies You may not post attachments You may not edit your posts BB code is On Smilies are On [IMG] code is On HTML code is Off Forum Rules
 Forum Jump User Control Panel Private Messages Subscriptions Who's Online Search Forums Forums Home Welcome     XP Math News     Off-Topic Discussion Mathematics     XP Math Games Worksheets     Homework Help     Problems Library     Math Challenges

All times are GMT -4. The time now is 08:25 AM.

 Contact Us - XP Math - Forums - Archive - Privacy Statement - Top XP Math